Economic Development in the 21st Century - Carmel U. Chiswick (Global Labor Organization (GLO), 2025)
The goal of economic development is to raise standards of living in LDCs, to be achieved by accumulating both human and non-human capital so as to maximize production net of the cost of these investments. An LDC economy is modelled with two sectors, modern and traditional, each of which uses its own type of human and non-human capital in production. Sector-specific human capital is specified as an attribute embodied in its workers, who have agency to choose their sector of employment and level of education. Earnings of labor are the sum of two components: recovery of human capital investment costs (e.g., student loan repayments) and an economic rent (i.e., profit) available for current consumption. The consumption-maximizing resource allocation equalizes rates of return to investments in all types of capital and allocates workers between the two sectors so that labor rents (i.e. consumption levels) are the same in both. Policy implications emphasize removing economic, social and cultural barriers to economic mobility for all resources.
Keywords: I25; I26; J21; J24; O00; O15; O41; 330; Economic development; growth; human capital; LDCs; labor rents